Nanoparticles (NPs)-mediated systemic mRNA delivery to reverse trastuzumab resistance for effective breast cancer therapy - Zhihui Dong; Zhuoshan Huang; Senlin Li; Ying Wang; Yandan Yao; Xianzhu Yang; Xiaoding Xu (Elsevier, 2023)
Monoclonal antibody-based therapy has achieved great success and is now one of the most crucial therapeutic modalities for cancer therapy. The first monoclonal antibody authorized for treating human epidermal growth receptor 2 (HER2)-positive breast cancer is trastuzumab. However, resistance to trastuzumab therapy is frequently encountered and thus significantly restricts the therapeutic outcomes. To address this issue, tumor microenvironment (TME) pH-responsive nanoparticles (NPs) were herein developed for systemic mRNA delivery to reverse the trastuzumab resistance of breast cancer (BCa). This nanoplatform is comprised of a methoxyl-poly (ethylene glycol)-b-poly (lactic-co-glycolic acid) copolymer with a TME pH-liable linker (Meo-PEG-Dlinkm-PLGA) and an amphiphilic cationic lipid that can complex PTEN mRNA via electrostatic interaction. When the long-circulating mRNA-loaded NPs build up in the tumor after being delivered intravenously, they could be efficiently internalized by tumor cells due to the TME pH-triggered PEG detachment from the NP surface. With the intracellular mRNA release to up-regulate PTEN expression, the constantly activated PI3K/Akt signaling pathway could be blocked in the trastuzumab-resistant BCa cells, thereby resulting in the reversal of trastuzumab resistance and effectively suppress the development of BCa.